Proposal for a low-cost personal protective equipment (PPE) to protect health care professionals in the fight against coronavirus - SERRA, Jhonathan Alexandre Furtado Meninea (2025)
The global situation caused by a coronavirus in 2020 has become an unprecedented health crisis. Since 1918, during the Spanish flu, Brazilian society haven’t seen a pandemic disease. Among the many individuals exposed to the virus, healthcare professionals are essential workers who fight the disease. However, due to the lack of previous investments in the public health sector in Brazil, several obstacles are evident, such as the reduced number of Personal Protective Equipment (PPE) available for healthcare professionals who have direct contact with those affected by the disease. Therefore, undergraduate students and professors from UFPA (Universidade Federal do Pará – Federal University of Pará) Biomedical Engineering program course mobilized to create solutions to this problem through the study and production of a low-cost face shield model, which proved to be essential in helping professionals, in addition to engaging several students in the social causes. Similar initiatives like this took place in states in southeastern Brazil, through the making of PPE in 3D printers from PLA (polylactic acid) or ABS (Acrylonitrile Butadiene Styrene) filaments, which can take hours to be ready. Therefore, the present study presents a handmade model to promote higher cost-benefit and shorter manufacturing time. To measure how this PPE proposed here affected the daily work of these professionals, this study performed a feedback form focused on the professionals who used the handmade model. Also, a comparison between the 3D printed vs the handmade model was done. The study showed that 69,5% of the respondents, which were professionals working in the health field, felt more protected with the handmade face shield. Finally, for this research, it is possible to say that the handmade faceshields have proven to be effective, providing confidence when used by the research participants.